First report of the occurrence of Acartia tonsa (Copepoda: Calanoida) in the Lesina lagoon (south Adriatic Sea- Mediterranean Sea). - Sei, S. & I. Ferrari (JMBA2 - Biodiversity Records, 2006)
The first occurrence of Acartia tonsa in a southern Adriatic Sea lagoon (Lesina lagoon) is reported. It was recorded in samples collected during two sampling campaigns carried out in May and July 2004. The arrival of A. tonsa may have caused the disappearance of the formerly abundant A. margalefi.